2018
DOI: 10.1097/qad.0000000000001914
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative plasma HIV burden disparities among adults in HIV care

Abstract: Although 95% of the cohort of adults in HIV care in San Francisco self-reported ART use during MMP interview, they spent on average almost 1 month per year at a transmittable viral level. We identified characteristics of those who were more likely to have higher viral burden, highlighting priorities for resource allocation to reduce onward HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Several studies have reported that PWID, PWID-MSM, younger persons, and homeless persons spent more time viremic compared with other transmission groups, older, and housed persons. 12–15,27 Although these subpopulations were not associated with delayed or no ART initiation in our secondary analysis, others have shown that they have lower rates of retention in care and thus adherence to ART, 28–30 which is likely a contributing factor for our findings. Furthermore, although the number of new HIV diagnoses decreased in recent years, including among vulnerable subpopulations, some groups such as PWID saw smaller decreases in new diagnoses over time compared with MSM.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Several studies have reported that PWID, PWID-MSM, younger persons, and homeless persons spent more time viremic compared with other transmission groups, older, and housed persons. 12–15,27 Although these subpopulations were not associated with delayed or no ART initiation in our secondary analysis, others have shown that they have lower rates of retention in care and thus adherence to ART, 28–30 which is likely a contributing factor for our findings. Furthermore, although the number of new HIV diagnoses decreased in recent years, including among vulnerable subpopulations, some groups such as PWID saw smaller decreases in new diagnoses over time compared with MSM.…”
Section: Discussionmentioning
confidence: 62%
“…We also found that less time spent above 10,000 copies per milliliter was associated with Asian/Pacific Islander race compared with whites, although in our secondary multivariate analysis, Asian/Pacific Islanders were not less likely than whites to have delayed or no ART initiation. We could not compare this finding with other similar studies because Asians and Pacific Islanders were included with other races, 12–14,16 but in 1 of these studies, persons of “other race,” which likely would have included Asians and Pacific Islanders, were associated with less time viremic. 16 Furthermore, we found Latinos were less likely to have delayed or no ART initiation but were not associated with less time spent above the viral thresholds compared with whites.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations